Childbirth at Sea and the question of nationality: A maqasid shariah analysis of jus soli and jus sanguinis - Abolaji, Abdulraheem Taofeeq; Abdulkadir, Abdulrazaq O.; Olohungbebe, Mamudat I. (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
Abstract The determination of nationality for children born aboard maritime vessels in international waters presents complex jurisdictional challenges that existing international legal frameworks inadequately address. Current applications of jus soli (right of soil) and jus sanguinis (right of blood) principles often create legal ambiguities, potential statelessness, and family separation in maritime contexts. While international maritime law provides some guidance through flag state jurisdiction, significant gaps remain in protecting the rights of children born in international waters, particularly when parents hold different nationalities or lack clear legal status. This article examines how the Islamic legal philosophy of Maqasid al-Shariah can inform and enhance the application of principles for determining nationality in maritime contexts. It also employs a qualitative doctrinal analysis, combining classical and contemporary Islamic legal sources with comparative international law methodology. It is found that there should be significant convergence between Maqasid al-Shariah objectives and international human rights principles, particularly regarding child protection, family unity, and human dignity. The analysis demonstrates that both jus soli and jus sanguinis find support within the Maqasid framework, but their application must be contextual and hierarchically prioritized.